Inclusive education: Ideas vs reality - Jovanović-Popadić Ana M. (Visoka škola strukovnih studija za vaspitače, Kruševac, 2016)
This paper discusses some of the key factors significant for the process of implementation of inclusive education in Serbia. After a brief review of the legal provisions regulating inclusive education in our country, the results of the research of attitudes towards inclusive education of teachers from six primary schools and one school for students with disabilities, as well as their experience, competencies, working conditions and opinions on consequences of inclusive education and education of children with developmental disabilities in specialized educational institutions are shown. Research was conducted in Krusevac, on a random sample of 60 teachers (51 teachers from primary schools and 9 special education teachers from schools for students with disabilities). We used two forms of questionnaires with twenty questions, and the results show predominantly negative attitudes towards inclusion in the majority of teachers in the sample. A significant percentage of respondents in both sub-samples considered that education of children with developmental disorders in specialized institutions (schools) may give better results, primarily due to a lack of systematic support to teachers of primary schools in the process of implementing educational inclusion. The conclusion provides a critical overview of the current situation and presents the potential solutions to the problems that were identified during the research, and refer to the unsustainability of the current practice of inclusive education in Serbia.